Effectiveness of flipped language learning classrooms and students’ perspectives - Munassir Alhamami; Mohsin Raza Khan (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2019)
The objectives of this study are to investigate the usefulness of the flipped language learning approach in a reading course, and to understand students’ attitudes and self-efficacy toward it. A quasi-experimental pretest-post-test design was employed. Two treatments were designed, namely, face-to-face and online, using the flipped classroom approach. A total of 43 students participated in the pre-tests and post-tests, administered in both treatments. The data were collected from the results of pre-tests and post-tests. A regression test and t-tests were performed to analyze the data. A significant difference was observed between the students’ results in the pre-tests and post-tests in both treatments. However, the post-test results in both treatments show no significant difference. This finding indicates that both face-to-face and flipped classroom approaches can be equally effective in enhancing the reading skill of Level 1 students. The survey results also indicate that students have more positive attitudes toward the flipped learning approach than society in general does toward it. Accordingly, teachers are advised to select a language-teaching approach that is helpful for students. They should also consider the perspectives of students. Improvement in reading skill is not necessarily attributed to only one of the approaches analyzed in this study.